Prefabrication of a functional bone graft with a pedicled periosteal flap as an in vivo bioreactor. Issue 1 (December 2017) - Huang, Ru-Lin; Tremp, Mathias; Ho, Chia-Kang; Sun, Yangbai; Liu, Kai; Li, Qingfeng
Abstract Thein vivo bioreactor principle, which focuses on using the body as a living bioreactor to cultivate stem cells, bioscaffolds, and growth factors and leveraging the body's self-regenerative capacity to regenerate new tissue, has been considered a potential approach for bone defect reconstruction. The histological characteristics of the periosteum allow it to possess a remarkable capacity to induce bone growth and remodeling, making it suitable as anin vivo bioreactor strategy for bone graft prefabrication. The present study was designed to prefabricate vascularized bone grafts using pedicled periosteal flaps and decellularized bone matrix (DBM) scaffolds in a rabbit model. The muscular pouches created in the femoral muscle were acted as a control. Our histological results revealed that both the periosteal flap group and muscular pouch group induced bone tissue formation on the DBM surface at both 8 and 16 weeks postoperatively. However, micro-computed tomography (microCT) scanning, biomechanical, and histomorphometric findings indicated that bone grafts from the periosteal flap group showed larger bone mass, faster bone formation rates, higher vascular density, and stronger biomechanical properties than in the muscular pouch group. We suggest that using the pedicled periosteal flap as anin vivo bioreactor is a promising approach for functional bone graft prefabrication.